let K be Field; :: thesis: for M1, M2, M3 being Matrix of K st len M1 = len M2 & len M2 = len M3 & width M1 = width M2 & width M2 = width M3 & M1 - M3 = M2 - M3 holds
M1 = M2

let M1, M2, M3 be Matrix of K; :: thesis: ( len M1 = len M2 & len M2 = len M3 & width M1 = width M2 & width M2 = width M3 & M1 - M3 = M2 - M3 implies M1 = M2 )
assume that
A1: len M1 = len M2 and
A2: len M2 = len M3 and
A3: width M1 = width M2 and
A4: width M2 = width M3 and
A5: M1 - M3 = M2 - M3 ; :: thesis: M1 = M2
A6: ( len (- M3) = len M3 & width (- M3) = width M3 ) by MATRIX_3:def 2;
per cases ( len M1 > 0 or len M1 = 0 ) by NAT_1:3;
suppose A7: len M1 > 0 ; :: thesis: M1 = M2
then A8: M2 is Matrix of len M1, width M1,K by ;
A9: M3 is Matrix of len M1, width M1,K by ;
(M1 + (- M3)) + M3 = M2 + ((- M3) + M3) by ;
then (M1 + (- M3)) + M3 = M2 + (M3 + (- M3)) by ;
then (M1 + (- M3)) + M3 = M2 + (0. (K,(len M1),(width M1))) by ;
then (M1 + (- M3)) + M3 = M2 by ;
then M1 + ((- M3) + M3) = M2 by A1, A2, A3, A4, A6, MATRIX_3:3;
then M1 + (M3 + (- M3)) = M2 by ;
then A10: M1 + (0. (K,(len M1),(width M1))) = M2 by ;
M1 is Matrix of len M1, width M1,K by ;
hence M1 = M2 by ; :: thesis: verum
end;
suppose len M1 = 0 ; :: thesis: M1 = M2
hence M1 = M2 by ; :: thesis: verum
end;
end;